Development and evaluation of a didactic game related to beekeeping in Spanish teaching as a Foreign Language (Research, Society and Development, 2020)
The study aim to analyze a didactic game used as a tool in order to promote content integrating and contextualization of Spanish Language and the discipline Alternative Cultures. The research context is a professional course in agriculture integrated to high school degree of a public school located in a small city in Mato Grosso do Sul state. For the game development it was took in consideration the students needs about the acquisition of Spanish Language in the Apiculture workplace sector and the goal of Federal Institute to promote professional training through the integration of technique and literacy knowledges. During the process of creating the didactic game it was necessary to observe practical lessons in the apiary sector of the school, to take note and describe the management procedures of the apiary. In the evaluation stage, it was involved 16 students from the second year of agriculture course integrated to high school degree. They organized and applied a questionnaire. It was concluded that didactic game is attractive, enables integration, awakens motivation among learners and it promotes significant Spanish Language learning.